Religious participation of persons with disabilities in Java, Indonesia: An explorative study - Sara Franssen; Irwanto Irwanto; Huib Cornielje (The Center for Disability Studies and Services Brawijaya University, 2020)
This descriptive qualitative study aims to explore the main physical and social barriers to accessibility of religious sites, services, and activities for people with physical disabilities in Indonesia and subsequently aims to explore possibilities to enhance their religious participation. A total of 28 interviewees participated in this research i.e., 16 self-indicated as Muslims and 12 as Christians. Among the male participants (n=16) were 10 Muslims and 6 Catholics, and among the female participants (n=12) were 6 Muslims and 6 Christians. Interviews and physical audits suggest serious need for improvements in accessibility and accommodation going to and within the establishment. Although majority of disabled persons interviewed for this study regularly participate in religious activities, they also notice that their basic needs and concerns are not being treated as priorities. Discourse on disability issues should be initiated and developed to create inclusive religious atmosphere.